A longitudinal study of exercise-induced bronchoconstriction and laryngeal obstruction in high school athletes - Ersson, K.; Mallmin, E.; Nordang, L.; Malinovschi, A.; Johansson, H. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Background Exercise-induced bronchoconstriction (EIB) and exercise-induced laryngeal obstruction (EILO) are common in elite athletes. Knowledge of which factors are related to incident EIB and EILO is limited. The aim of this study was to explore the course of EIB and EILO in adolescent athletes over a 2 years period and baseline characteristics related to incident EIB.